Zimbabwe : Zimbabwe: Settlement of Overdue Financial Obligations to the Poverty Reduction and Growth Trust,Lifting of Declaration of Noncooperation, Lifting of Restriction on Fund Technical Assistance, and Restoration of Poverty Reduction and Growth Trust Eligibility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Zimbabwe's Settlement of Overdue Financial Obligations to the Poverty Reduction and Growth Trust (PRGT), Lifting of Declaration of Noncooperation, Lifting of Restriction on IMF technical assistance, and restoration of PRGT eligibility. In light of Zimbabwe's settlement of its overdue financial obligations to the PRGT, the IMF staff proposes that the Board remove the remaining remedial measures. Zimbabwe is eligible to return to the PRGT-eligibility list. The IMF staff also proposes that the Board lift the declaration of noncooperation, remove the remaining restriction on the provision of IMF technical assistance, and reinstate Zimbabwe as a PRGT-eligible country.